Peculiarities and challenges of double degree programs between Japanese and Russian medical schools - Shihoko Yamakawa; Olga Razvina; Fumiko Okazaki; Hiroshi Hibino; Toshiyuki Someya; Tatsuo Ushiki (The Asia Pacific Scholar)
Introduction: Niigata University School of Medicine and Niigata University Graduate School of Medical and Dental Sciences have been engaging in medical exchanges with Russian medical universities for over 30 years. In 2015, a double-degree program with Russian medical universities was initiated, leading to a multi-layered education project that included short-term undergraduate student exchange programs and graduate-level double-degree programs, resulting in the circulation of human resources. Methods: The program was conducted in English, and a maximum of 15 credits could be transferred based on the universities' regulations. Degree examinations were conducted independently, and successful candidates were awarded degrees from both Niigata University and their home university in Russia. The project was overseen by the G-MedEx Centre at Niigata University, which included staff with international experience. Results: The difference in standard study duration between Japan and Russia was eliminated by using a four-year system in the graduate school doctoral programs. Three study models were proposed by Russian universities, considering each university's regulations and various circumstances. The curriculum was determined based on the rules of the universities in Russia and the circumstances of the students. Agreements were made with each university in supplementary documents. Conclusion: Despite the differences in educational standards and the lack of a common educational framework between Japan and Russia, the difficulties can be overcome, and educational compatibility can be increased.